2021
DOI: 10.31235/osf.io/wuq6n
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pedagogical Effects of Social Media on Iraqi Kurd EFL learners

Abstract: English language learners use social media platforms for improving their language skills through exchanging ideas, sharing their thoughts, and getting exposed to authentic language. The use of social media by learners might yield positive or adverse effects. This study, therefore, explores the pedagogical consequences of some social media platforms on Iraqi Kurd EFL learners. It Highlights the significant impacts of social media on learning English, vocabulary, and spelling. It explicitly attempts to discover … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Several study results asserted the positive role of social media platforms in improving Kurdish EFL learners' English language skills mainly in an informal way. A study by Nuri et al (2021) examined the impact of social media platforms on Kurdish EFL learners' English language development. The results of this study indicated that social media platforms generally help learners to learn English in an informal not academic way.…”
Section: Previous Studies On Language Learning Applications and Mobil...mentioning
confidence: 99%
“…Several study results asserted the positive role of social media platforms in improving Kurdish EFL learners' English language skills mainly in an informal way. A study by Nuri et al (2021) examined the impact of social media platforms on Kurdish EFL learners' English language development. The results of this study indicated that social media platforms generally help learners to learn English in an informal not academic way.…”
Section: Previous Studies On Language Learning Applications and Mobil...mentioning
confidence: 99%